Relatively high interest but limited active engagement in HIV cure research: Awareness, interest, and information-seeking among affected communities in the Netherlands - Maaike A.J. Noorman; John B.F. de Wit; Tamika A. Marcos; Sarah E. Stutterheim; Thijs Albers; Kai J. Jonas; Chantal den Daas (Journal of Virus Eradication)
Background: Community engagement is important for inclusive HIV cure development. This study evaluates current engagement in HIV cure research among affected communities in the Netherlands by analyzing awareness, interest, and information-seeking behavior. It also identifies participant characteristics and HIV-related illness perceptions linked to each engagement stage. Methods: A cross-sectional survey was conducted from July 2023 to March 2024, involving 499 people with HIV and 578 individuals without HIV, including partners and gay, bisexual, and other men who have sex with men. Multivariate regression analyses examined the relationships between participant characteristics, HIV-related illness perceptions, and three outcomes: awareness, interest, and information-seeking. Results: The mean awareness was 3.08 (SD = 0.99) interest was higher at 3.67 (SD = 0.85), while the information-seeking frequency was lower at 2.33 (SD = 0.97). Higher awareness was seen in older participants, non-cisgender men, and those with increased perceived control and comprehensibility of HIV. Interest in cure research was higher among people with HIV, those with a migration background, individuals with steady partner(s), and those experiencing greater HIV-related concerns, negative HIV-related emotions, and better HIV comprehension. Information-seeking frequency was greater among people with HIV, those with a bachelor's degree, individuals from a migration background, those with steady partner(s), and those perceiving more severe HIV-related symptoms, and heightened concerns and negative emotions about HIV. Conclusion: While moderate awareness exists, engagement remains passive with limited information-seeking; however, significant interest in a cure underscores the need for enhanced communication efforts to foster inclusive HIV cure development.